To study the effect of plasma treatment on storage fungi of Mung bean (Vigna radiata) - Saru (My University, 2016)
This study focuses on the inactivation of Aspergillus flavus from the surface of the mung bean by using the low pressure cold plasma. Before decontamination process, the sample is inoculated with the 106 spores of Aspergillus flavus. The plasma treatment of the sample is carried out by using the SF6 gas for the duration of 2-10min. There is 1 log reduction of the spores after 2 minute treatment and further increases to 2-Log reduction after 5 min of plasma treatment. Complete decontamination of the spores from the mung bean surface is achieved within 10 minutes of treatment. Various biochemical parameters of the mung bean sample are also investigated to study the effect of plasma treatment on the nutritional value of the sample. The cooking time of the mung bean sample is decreased from 35 to 30 minutes due to increase in the water uptake ratio of the plasma treated sample. Ash content of the mung bean predicts the mineral present inside the mung bean and it is found to be increased after plasma treatment. Proximate analysis of the sample has been also investigated and it is notice that the protein, fat and carbohydrate content of the mung bean is increased from 27% to 30 %, 1.30 %to 1.80%, and 1.186 to 1.1935μg/ml respectively. FTIR and SDS-PAGE of the treated and untreated sample is compared and there is no change in the peaks of FTIR and the protein bands of the SDS-PAGE. Antioxidant activity of the untreated and plasma treated mung bean sample is studied and it results in the increase of the total phenolic and flavonoid content of the mung bean. Radical scavenging activity of the sample is also carried out by the FRAP and DPPH assay and it is observed that scavenging activity of the mung bean sample enhanced. Tetrazolium staining was performed and it is observed that the 98% of the seeds are viable after plasma treatment.
Master of Technology -Biotechnology
Keywords: Aspergillus flavus; Mung bean; Plasma treatment; Storage fungi; aflatoxins